Lactococcus lactis Catherter-Related Bloodstream Infection in an Infant : Case Report - (:unkn) unknown (NATL INST INFECTIOUS DISEASES, 2015)
Lactococcus lactis is a gram-positive coccus that is nonpathogenic in humans. Herein, we present the case of a 1-year-old boy with Down syndrome and Hirschprung's disease (HD) who developed a catheter-related bloodstream infection with L. lactis after gastrointestinal surgery. The patient had been hospitalized in the pediatric surgery unit from birth because of HD, and had undergone the Duhamel-Martin procedure which caused recurrent diarrhea episodes and feeding intolerance. On the infant's 430th day of life, he had an episode of gastroenteritis and feeding intolerance. Because of clinical suspiction of sepsis, blood cultures were taken both from the central venous catheter and peripheral vein, and evidence of a growing microorganism was detected in 2 different central venous catheter blood cultures taken 2 days apart. The colonies were then identified by both the Vitek 2 and Vitek MS systems (bioMerieux, Marseille, France) as L. lactis spp. lactis. The central venous catheter could not be removed because of the absence of a peripheral venous line, and the patient was subsequently successfully treated with vancomycin. Therefore, although Lactococcus species is generally thought to be nonpathogenic, it should still be kept in mind as a potential pathogen in infants.
Keywords: RAPID IDENTIFICATION; CREMORIS